Safety, efficacy, gastrointestinal tolerance, and digestibility of brewed chicken protein in healthy adult dogs - Smola, Meredith A.; Oba, Patrícia M.; Mioto, Julio C.; Audibert, Pernilla; Belloso, Tomas; Swanson, Kelly S. (Frontiers in Veterinary Science, 2025)
IntroductionProducing enough protein continues to be a challenge, but alternatives may provide economic and ecological relief. Sufficient testing is necessary to confirm safety and evaluate nutritional value. Our objective was to evaluate the safety, efficacy, gastrointestinal tolerance, and apparent total tract digestibility (ATTD) of brewed chicken protein (BCP; Saccharomyces cerevisiae expressing a chicken protein).MethodsThirty-two healthy adult dogs (BW = 9.68 ± 1.18 kg; age = 4.16 ± 1.85 yr) were used in a completely randomized design (n = 8/treatment). After a 2-wk acclimation phase, baseline measurements were collected and dogs were allotted to the following treatments and fed for 26 wk: control diet (0% BCP; Control), 15% BCP (Low), 30% BCP (Medium), or 40% BCP (High). Palatability was assessed by comparing dry diets coated with 0% (control) vs. 1% BCP in 20 adult dogs. Data were analyzed using the Mixed Models procedure of SAS 9.4, with p < 0.05 being significant and trends accepted at p < 0.10.ResultsConsumption of BCP did not affect food intake, BW, physical parameters, serum chemistry, hematology, and urinalysis. The dry matter, organic matter, and crude protein ATTD were greater (p < 0.05) for High, while the fat ATTD was greater (p < 0.05) for Control. Fecal output was lower (p < 0.0001) and fecal dry matter was lower (p < 0.001) for dogs fed High. Fecal acetate concentrations were lower (p < 0.05) and propionate concentrations tended to be higher (p = 0.06) in dogs fed BCP. Fecal isobutyrate, isovalerate, indole, total phenol and indole, and ammonia concentrations were lower (p < 0.001) and fecal valerate concentrations were higher (p < 0.0001) in dogs fed BCP. Fecal bacterial alpha diversity was lower (p < 0.05) in dogs fed BCP. For beta diversity, dogs fed Control were different than those fed BCP. Over 20 fecal bacterial genera were affected by BCP consumption. Palatability of BCP was high (p < 0.05; 2.93:1 consumption ratio).ConclusionThese results indicate that the BCP ingredient tested is an effective source of protein that is safe for use in adult dog foods at an inclusion level of up to 40%. No detrimental effects were observed, and notable changes to nutrient digestibility and fecal characteristics, metabolites, and microbiota populations suggest potential benefits on gastrointestinal health.